SUBJECTS ROAD TO SUBALTERNITY IN BALÚN-CANÁN (1957) BY ROSARIO CASTELLANOS - Sánchez Echevarría, Keren Heiddy (2022)
In this article we will address the novel Balún-Canán (1957) written by Rosario Castellanos, on the one hand, our analysis will focus on two female characters that we consider key within the plot, these are Matilde and the girl (whose identity is removed by not naming it). We believe that these female subjects, despite belonging to a high social class, either by their decisions or by the decisions of external agents, are destined to subalternity, an aspect that is announced from the beginning. On the other hand, we will also examine how subordinate subjects can find a space within literature, such as the representation that women do not have in the plot is obtained by establishing themselves as narrators of the novel.